Respuesta del psicoanálisis al individualismo moderno y la tendencia a la biologización del diagnóstico psicológico - Kevin Ramiro, Andrade Gómez (2021)
ABSTRACT: The aim of this research work is to analyze the epochal diagnosis in order to propose a theoretical-clinical alternative from psychoanalysis, for which two fundamental tendencies were identified that condition a particular modality of discomfort and suffering in today´s Western society: Modern individualism and the trend towards biologization. The bibliographic review with a qualitative approach methodology was used of a documentary nature and descriptive; The sample was of an intentional non-probabilistic type made up of 53 documents, consisting of scientific articles, books, seminars and theses, published between 2011-2021 in scientific databases such as Dialnet, Scopus, Scielo, Redalyc and Apola. The results shows that modern individualism has the effects of depression, madness, burnout syndrome, estrangement from the other, nihilism, disappointment, apathy and the imperatives of performance, authenticity and self-determined freedom; Concerning the trend towards biologization, it was found that it represents an important theoretical-clinical problem-solving to address in the area of mental health from an interdisciplinary perspective, due it reduces human suffering to a biological dimension and eliminates the meanings of life subjective and discomfort, putting aside their social, biographical, historical and institutional conditions, leading to medicalization. Conclusion: Lacan's theoretical model allows the development of a proposal that is based on thinking the human from a discursive link that opposes the suffering effect of the diagnosed tendencies. Keywords: Individualism, biologization, subject, psychoanalysis